Mechanism of ginsenoside Rg1 renal protection in a mouse model of d-galactose-induced subacute damage. (1st September 2016) - Fan, Yanling; Xia, Jieyu; Jia, Daoyong; Zhang, Mengsi; Zhang, Yanyan; Huang, Guoning; Wang, Yaping
Abstract: Context Ginseng is a widely used herbal medicine in China but its mechanism of action remains unclear. Objective The objectives of this work were to study the protective effect of ginsenoside Rg1 on subacute murine renal damage induced byd -galactose and its mechanism. Materials and methods C57BL/6J mice were injected with 120 mg/kg/d (sc)d -galactose for 1 week, followed by a combined treatment of Rg1 20 mg/kg/d (ip) and 120 mg/kg/dd -galactose (sc) for 5 weeks. Mice were injected with the 0.9% saline 0.2 mL/d (sc) and 120 mg/kg/dd -galactose (sc) for 6 weeks in the control group and thed -galactose group, respectively. After 6 weeks, urea, creatinine, uric acid, cystatin (Cys-C), senescence-associated β-galactosidase (SA-β-gal) staining positive kidney cells, superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), malondialdehyde (MDA), glycation end products (AGEs) and 8-hydroxy-2 deoxyguanosine (8-OH-dG) were measured. Results Treatment with Rg1 ameliorated kidney function and aging state (urea from 17.19 ± 1.09 to 15.77 ± 1.22 mmol·L − 1, creatinine from 29.40 ± 5.72 to 22.60 ± 3.97 μmol·L − 1, uric acid from 86.80 ± 5.97 to 72.80 ± 10.61 μmol·L − 1, Cys-C from 0.23 ± 0.03 to 0.18 ± 0.05 mg·L − 1, ROD of SA-β-gal from 56.32 ± 10.48 to 26.78 ± 7.34, SOD from 150.22 ± 19.07 to 190.56 ± 15.83 U·(mg·prot) −1, MDA from 9.28 ± 1.59 to 3.17 ± 0.82 nmol·(mg·prot) −1, GSH-PX from 15.68 ± 2.11 to 20.32 ± 2.96 U·(mg·prot) −1 as well as regulated glomerulus morphology (glomerulus diameter from 775.77 ± 18.41 to 695.04 ± 14.61 μm, renal capsule width from 39.56 ± 3.51 to 31.42 ± 2.70 μm, glomerulus basement membrane from 206.03 ± 16.22 to 157.27 ± 15.70 nm, podocyte slit from 55.21 ± 8.55 to 37.63 ± 6.65 nm). Conclusions Ginsenoside Rg1 can antagonised -galactose subacute renal damage in mice and this may occur due to alleviating oxidative stress injury.